2019
DOI: 10.3389/fimmu.2019.00917
|View full text |Cite|
|
Sign up to set email alerts
|

The Emerging Role of Myeloid-Derived Suppressor Cells in Tuberculosis

Abstract: Myeloid cells are crucial for the host control of a Mycobacterium tuberculosis ( M.tb ) infection, however the adverse role of specific myeloid subsets has increasingly been appreciated. The relevance of such cells in therapeutic strategies and predictive/prognostic algorithms is to promote interest in regulatory myeloid cells in tuberculosis (TB). Myeloid-derived suppressor cells (MDSC) are a heterogeneous collection of phagocytes comprised of monocytic- and polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 71 publications
(136 reference statements)
3
49
0
Order By: Relevance
“…Our study has evaluated bacterial internalization at a range of MOIs that includes low numbers of bacteria, and with a clinically relevant strain of E. coli responsible for invasive infections, such as sepsis and meningitis (Yao, Xie, & Kim, 2006). Additionally, two other studies have reported the internalization of M. tuberculosis and M. bovis BCG by MDSCs, again in agreement with our results (Agrawal et al, 2018; Magcwebeba et al, 2019; Martino et al, 2010). However, our study rigorously addressed the kinetics, frequency, and abundance of internalization using fluorescence microscopy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study has evaluated bacterial internalization at a range of MOIs that includes low numbers of bacteria, and with a clinically relevant strain of E. coli responsible for invasive infections, such as sepsis and meningitis (Yao, Xie, & Kim, 2006). Additionally, two other studies have reported the internalization of M. tuberculosis and M. bovis BCG by MDSCs, again in agreement with our results (Agrawal et al, 2018; Magcwebeba et al, 2019; Martino et al, 2010). However, our study rigorously addressed the kinetics, frequency, and abundance of internalization using fluorescence microscopy.…”
Section: Discussionsupporting
confidence: 93%
“…Davis and colleagues briefly suggested that MDSCs can phagocytose Escherichia coli ( E. coli ) particles in vitro ; however, the mechanistic details were not analyzed in depth (Davis, Silvin, & Allen, 2017). Additionally, two other studies reported that MDSCs can internalize Mycobacterium tuberculosis and Mycobacterium bovis Bacillus Calmette-Guerin (BCG), although the mechanisms, kinetics, and efficiency of internalization were not addressed (Agrawal et al, 2018; Magcwebeba, Dorhoi, & du Plessis, 2019; Martino et al, 2010). As such, our mechanistic understanding of direct MDSC interactions with bacterial pathogens has remained limited, and the consequences during infection have been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…First, these cells have known immunoregulatory functions and have been shown to secrete IL10 25 , a cytokine which inhibits protective T-cell responses in Mycobacterium avium infected mice 26 . More generally, granulocytes can act as myeloid-derived suppressor cells (MDSCs) capable of inhibiting a protective adaptive immune response via suppression of T-cell function 27 29 . Alternatively, neutrophils are also phagocytes capable of providing a permissive niche for intracellular Mtb replication 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The chronic, low-grade inflammation of many solid tumors is the dominant driving force for MDSC accumulation , leading investigators in noncancer fields to explore if MDSC are involved in other inflammatory settings. MDSC were found to expand in patients and mice in noncancer pathological settings, such as bacterial and viral infection (O'Connor et al 2017, Ost et al 2016 including HIV/AIDS (Gama et al 2012) and tuberculosis (Magcwebeba et al 2019); sepsis (Schrijver et al 2019); and autoimmune diseases including lupus erythematosus (Florez-Pollack et al 2019), arthritis (Zhang et al 2015), and inflammatory bowel disease (Kontaki et al 2017). MDSC also expand in normal physiological settings where immune suppression is important, such as pregnancy, where they facilitate maternal-fetal tolerance (Kostlin et al 2014, Pan et al 2016.…”
Section: Introductionmentioning
confidence: 99%